2021
DOI: 10.1097/der.0000000000000822
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Fragrance Contact Allergy Among Turkish Population: A 24-Year, Cross-Sectional, Tertiary Single-Center, Retrospective Study

Abstract: Background: Limited data exist on fragrance contact allergy among Turkish population. Objective: The aim of this study was to investigate the frequency and characteristics of fragrance contact allergy in Turkey. Methods: A retrospective cohort study was conducted on 2566 patients consecutively patch tested with the European baseline series and additionally with a fragrance series (n = 358) at a tertiary referral center between 1996 and 2019.Results: One hundred sixty-three patients (6.4%) (male/female, 1.5:1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
3
1
0
Order By: Relevance
“…We found the rate of fragrance mix sensitivity to be 3.4%, and it was significantly higher in men and individuals over 40 years of age. In other studies conducted in Turkey, sensitivity rates have been reported to range from 2.1% to 6.4% 4–8,24 . Similar to our study, in the literature, it is stated that fragrance mix sensitivity increases with age 23–26 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found the rate of fragrance mix sensitivity to be 3.4%, and it was significantly higher in men and individuals over 40 years of age. In other studies conducted in Turkey, sensitivity rates have been reported to range from 2.1% to 6.4% 4–8,24 . Similar to our study, in the literature, it is stated that fragrance mix sensitivity increases with age 23–26 .…”
Section: Discussionsupporting
confidence: 91%
“…In other studies conducted in Turkey, sensitivity rates have been reported to range from 2.1% to 6.4%. [4][5][6][7][8]24 Similar to our study, in the literature, it is stated that fragrance mix sensitivity increases with age. [23][24][25][26] This increase is considered to be due to the decrease in the protection of the skin-barrier and the increase in the use of topical moisturizers and cosmetics with advancing age.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The prevalence of contact sensitization was 1.62% -1.98%, demonstrating a significant reduction in HICC allergy in European dermatitis patients prior to the then impending European ban (23). In a retrospective study of patch tested patients between 1996 and 2019, conducted in Turkey, the prevalence of sensitization to HICC was found to be 0.5%, and occupational exposure was assumed as the main cause of sensitization in 6.1% of the clinically significant cases (24). The results obtained in our study confirm the role of occupational exposure for contact sensitization to HICC.…”
Section: Discussionmentioning
confidence: 96%